Mycotic skin lesions in an adult reindeer caused by Debaryomyces bansenii. A case report - Rehbinder, Claes; Mattsson, Roland (Rangifer, 1994)
This report apparently is the first to describe candidosis in reindeer. It is imperative that reindeer kept in corrals during winter and spring for supplementary feeding, are provided clean, dry conditions and that strict hygenic measures are followed. If reindeer on the other hand are kept in dirty, wet and muddy corrals, among other things, skin lesions due to fungal infections may possibly appear rather frequently.